COVID-19 Pandemic Impact on Dental Practice - Bozhkova, Tanya; Musurlieva, Nina (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: The COVID-19 pandemic has had a huge impact on the dentistry industry from the initial lockdown in March 2020 to the present day, nearly one year later with dentists unable to practice during the initial lockdown, that is when revenue took the biggest hit. The study aims to examine the impact of COVID-19 on dental practices during the pandemic in Bulgaria. Material and methods: A specially developed questionnaire was distributed electronically among 138 dentists from all regions of Bulgaria. The collected primary statistical information was entered and processed with the statistical package SPSS Statistics 19.0 Results: Statistical analyzes of the questionnaire show that (62,32%±4,12) of dentists say COVID-19 made no impact on their decision to retire or continue practicing; 43% of respondents predict revenue or costs will be the biggest challenge facing their practice in 2021. Part of dentists (34.78 % ± 4,05) believe that COVID-19 allowed them to learn more about infection control. Most of the respondents (87.68% ± 2.79) agree their income was lower in April to September of 2020 compared to 2019. More than half of dentists (61.59 % ± 4.14) believe Covid 19 has not impacted the products or services they offer. The majority of the participants (84.78 % ± 3.05) did not perform non-emergency procedures during the pandemic. Conclusion: Despite the numerous disadvantages caused by the COVID-19 pandemic, our survey shows dentists have found ways to adapt and succeed. Introduction: The COVID-19 pandemic has had a huge impact on the dentistry industry from the initial lockdown in March 2020 to the present day, nearly one year later with dentists unable to practice during the initial lockdown, that is when revenue took the biggest hit. The study aims to examine the impact of COVID-19 on dental practices during the pandemic in Bulgaria. Material and methods: A specially developed questionnaire was distributed electronically among 138 dentists from all regions of Bulgaria. The collected primary statistical information was entered and processed with the statistical package SPSS Statistics 19.0 Results: Statistical analyzes of the questionnaire show that (62,32%±4,12) of dentists say COVID-19 made no impact on their decision to retire or continue practicing; 43% of respondents predict revenue or costs will be the biggest challenge facing their practice in 2021. Part of dentists (34.78 % ± 4,05) believe that COVID-19 allowed them to learn more about infection control. Most of the respondents (87.68% ± 2.79) agree their income was lower in April to September of 2020 compared to 2019. More than half of dentists (61.59 % ± 4.14) believe Covid 19 has not impacted the products or services they offer. The majority of the participants (84.78 % ± 3.05) did not perform non-emergency procedures during the pandemic. Conclusion: Despite the numerous disadvantages caused by the COVID-19 pandemic, our survey shows dentists have found ways to adapt and succeed.